Association of N-Terminal Pro-B-Type Natriuretic Peptide With Contrast-Induced Nephropathy and Long-Term Outcomes in Patients With Chronic Kidney Disease and Relative Preserved Left Ventricular Function. Issue 13 (April 2015) - Liu, Yuan-hui; Liu, Yong; Zhou, Ying-ling; Yu, Dan-qing; He, Peng-cheng; Xie, Nian-Jin; Li, Hua-long; Wei-Guo,; Chen, Ji-yan; Tan, Ning
Abstract : Abstract: The aim of the present article was to evaluate the association of N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) with contrast-induced nephropathy (CIN) and long-term outcomes in patients with chronic kidney disease (CKD) and relative preserved left ventricular function (LVF) undergoing percutaneous coronary intervention (PCI). We prospectively enrolled 1203 consecutive patients with CKD and preserved LVF undergoing elective PCI. The primary end point was the development of CIN, defined as an absolute increase in serum creatinine (SCr) ≥0.5 mg/dL, from baseline within 48 to 72 hours after contrast medium exposure. CIN incidence varied from 2.2% to 5.2%. Univariate logistic analysis showed that lg-NT-pro-BNP was significantly associated with CIN (odds ratio [OR] = 3.93, 95% confidence interval [CI], 2.22–6.97, P < 0.001). Furthermore, lg-NT-pro-BNP remained a significant predictor of CIN (OR = 3.30, 95% CI, 1.57–6.93, P = 0.002), even after adjusting for potential confounding risk factors. These results were confirmed by using other CIN criteria, which were defined as elevations of the SCr by 25% or 0.5 and 0.3 mg/dL from the baseline. The best cutoff value of lg-NT-pro-BNP for detecting CIN was 2.73 pg/mL (537 pg/mL) with 73.1% sensitivity and 70.0% specificity according to the receiver operating characteristic (ROC) analysis (C statistic = 0.754, 95% CI, 0.67–0.84, P < 0.001). In addition, NT-pro-BNP ≥537 pg/mL (2.73 pg/mL, lg-NT-pro-BNP) was associated with an increased risk of all-cause mortality and composite end points during 2.5 years of follow-up. NT-pro-BNP ≥537 pg/mL is independently associated with an increased risk of CIN with different definitions and poor clinical outcomes in patients with CKD and relative preserved LVF undergoing PCI.